Structure and surface chemistry analysis of ultra-thin reactive ion etched GaAs (111) nanopillars - Riedl, Thomas; Kovács, A.; Meertens, D.; Lindner, Jörg

RBS of gold-coated polystyrene nanospheres - Rüsing, M.; Merten, L.; Reinert, P.; Rogalla, D.; Becker, H.-W.; Lindner, Jörg

TEM investigations on the nanoheteroepitaxy of semiconductors - Lindner, Jörg

Microscopic studies of plasmonic nanostructures II - Lindner, Jörg

Nanostrukturierte Oberflächen, nicht nur zum Spass - Lindner, Jörg

Radio Frequency Electromechanical Control over a Surface Plasmon Polariton Coupler - Ruppert, Claudia; Förster, Frederike; Zrenner, Artur; Kinzel, Jörg B.; Wixforth, Achim; Krenner, Hubert J.; Betz, Markus (ACS Photonics)
We explore the impact of ∼500 MHz surface acoustic waves traveling across a commensurable plasmonic grating coupler. A stroboscopic technique involving surface acoustic waves synchronized to a modelocked optical source allows to time-resolve the dynamical impact of the electromechanically induced perturbation. The surface acoustic wave periodically enhances or decreases the surface ripple of the static grating. Most remarkably, the dynamic surface deformation deliberately modulates the coupler’s efficiency by ±2% during the ∼2 ns acoustic cycle.
Keywords: nanomechanics; plasmonics; surface acoustic waves; surface plasmon polaritons

Symmetry-Selective Third-Harmonic Generation from Plasmonic Metacrystals - Chen, Shumei; Li, Guixin; Zeuner, Franziska; Wong, Wing Han; Pun, Edwin Yue Bun; Zentgraf, Thomas; Cheah, Kok Wai; Zhang, Shuang (Physical Review Letters)

Hochauflösende Holografie - Zentgraf, Thomas (Physik in unserer Zeit)

Optical Spectroscopy of Graphene Quantum Dots: The Case of C132 - Riesen, Hans; Wiebeler, Christian; Schumacher, Stefan (The Journal of Physical Chemistry A)

Quantum Yields and Reaction Times of Photochromic Diarylethenes: Nonadiabatic Ab Initio Molecular Dynamics for Normal- and Inverse-Type - Wiebeler, Christian; Schumacher, Stefan (The Journal of Physical Chemistry A)